2009
DOI: 10.1007/s00330-009-1600-6
|View full text |Cite
|
Sign up to set email alerts
|

64-Slice CT angiography of the abdominal aorta and abdominal arteries: comparison of the diagnostic efficacy of iobitridol 350 mgI/ml versus iomeprol 400 mgI/ml in a prospective, randomised, double-blind multi-centre trial

Abstract: PurposeThe purpose of this study was to assess the influence of iodine concentration on diagnostic efficacy in multi-detector-row computed tomography (MDCT) angiography of the abdominal aorta and abdominal arteries.MethodsIRB approval and informed consent were obtained. In this double-blind trial, patients were randomised to undergo MDCT angiography of the abdominal arteries during administration of iobitridol (350 mgI/ml) or iomeprol (400 mgI/ml). Each centre applied its own technique for delivery of contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…[1][2][3][4] One important aspect of abdominal CTA is the vasculature-to-background contrast. This iodine-based contrast can be increased when applying low-tube-voltages.…”
mentioning
confidence: 99%
“…[1][2][3][4] One important aspect of abdominal CTA is the vasculature-to-background contrast. This iodine-based contrast can be increased when applying low-tube-voltages.…”
mentioning
confidence: 99%
“…Corresponding to Bhatti et al [12] who found CTA superior to MRA in renal arteries, our data indicate the superiority of CTA over MRA and duplex US in the two mesenteric arteries. Loewe et al refer to the outstanding role of CTA as a safe, robust and reproducible modality for diagnosing diseased abdominal arteries, and they rated the broad majority of their evaluated abdominal arteries as of good or excellent image quality [13]. We found CTA to offer the best image quality among the four assessed modalities, rated 4.4 as also good to excellent imaging.…”
Section: Image Qualitymentioning
confidence: 55%
“…The most appropriate method to assess a new contrast agent is through scientific methodology in which it is evaluated in a blinded fashion by the individuals involved. This approach has been described in a few reports for iodine-based contrast agents (IBCAs) [15]. To our knowledge, no prior report has described objective blinded evaluation of GBCAs for acute adverse events as a primary end point and image quality.…”
Section: Introductionmentioning
confidence: 99%